Implications of the Utilization of Artificial Intelligence (AI) on Academic Ethics and Social Values of UIN Sultan Maulana Hasanuddin Banten Students - Tuti Musaropah; Amalia Az-Zahra; Erika Ulan Dari; Selnistia Hidayani (PT. Intelek Cendikiawan Nusantara, 2025)
The use of artificial intelligence (AI) in higher education affects students' learning efficiency, academic ethics, and social values. This study aims to analyze the relationship between AI and academic ethics and social values of students at Sultan Maulana Hasanuddin State Islamic University Banten, as well as examine students' perceptions and ethical practices in its use. The research uses a descriptive qualitative approach with the type of field research. Primary data was obtained through interviews, observations, and filling out questionnaires by students, analysis was carried out through transcription, reduction, thematic grouping, social interpretation, and descriptive narrative preparation, with the perspective of pedagogical paradox (contradictory situations) and UNESCO ethical principles as the basis of the analysis. The results show that students use AI quite well, but their analytical skills and the application of academic ethics are still limited. The social value of students is high in the aspect of tolerance, but cooperation and social concern need to be improved, emphasizing the importance of integrating AI ethics and character education based on Islamic values